The Effect of Teach-Back Training on Self Management in Kidney Transplant Recipients: A Clinical Trial - Farzin Mollazadeh; Masumeh Hemmati Maslakpak (Shiraz University of Medical Sciences, 2018)
Background: Kidney transplant recipients need self-management during their lifetime, and training these patients is essential for the realization of self-management. Teach-back training (TBT) was used to receive, understand, and retain information. This study aimed to determine the effect of TBT on self-management in kidney transplant recipients. Methods: In this clinical trial study, 84 kidney transplant recipients who referred to the clinic of Imam Khomeini Hospital in Urmia (a city in northwest of Iran), from January to March 2017, were selected through convenience sampling and randomly assigned to intervention and control groups. In the intervention group, educational content was presented for each patient with TBT in 5 sessions of 60 minutes. Data were collected before and after the intervention by a special Self-Management Questionnaire for Kidney Transplant Recipients in five areas as follows: self-monitoring, self-care behavior in daily living, early detecting and coping with abnormalities after kidney transplantation, stress management and the category of non-categorized area. This is a valid and reliable questionnaire (α=0.76). Collected data were analyzed by independent t-test and Mann-Whitney test. Statistical analysis was performed using SPSS 20 and P≤0.05 was considered as significant. Results: Independent t-test showed that the mean of self-management score between the control and intervention groups was not statistically significant before the intervention (P=0.90). The mean score of self-management increased after implementation of TBT in the intervention group compared to the control group, and the difference was statistically significant (P=0.001). Conclusion: The implementation of TBT method is effective in promoting self-management of kidney transplant recipients. Therefore, it is recommended that this method should be used to train the patients to better understand the components of self-management. Trial Registration Number: IRCT2016122817059N10